Altered zinc homeostasis in a primary cell culture model of the retinal pigment epithelium - Álvarez-Barrios, Ana; Álvarez, Lydia; Artime, Enol; García, Montserrat; Lengyel, Imre; Pereiro, Rosario; González-Iglesias, Héctor (Frontiers in Nutrition, 2023)
The retinal pigment epithelium (RPE) is progressively degenerated during age-related macular degeneration (AMD), one of the leading causes of irreversible blindness, which clinical hallmark is the buildup of sub-RPE extracellular material. Clinical observations indicate that Zn dyshomeostasis can initiate detrimental intracellular events in the RPE. In this study, we used a primary human fetal RPE cell culture model producing sub-RPE deposits accumulation that recapitulates features of early AMD to study Zn homeostasis and metalloproteins changes. RPE cell derived samples were collected at 10, 21 and 59 days in culture and processed for RNA sequencing, elemental mass spectrometry and the abundance and cellular localization of specific proteins. RPE cells developed processes normal to RPE, including intercellular unions formation and expression of RPE proteins. Punctate deposition of apolipoprotein E, marker of sub-RPE material accumulation, was observed from three weeks with profusion after two months in culture. Zn cytoplasmic concentrations significantly decreased 0.2 times at 59 days, from 0.264 ± 0.119 ng·µg-1 at 10 days to 0.062 ± 0.043 ng·µg-1 at 59 days (p<0.05). Conversely, increased levels of Cu (1.5-fold in cytoplasm, 5.0-fold in cell nuclei and membranes), Na (3.5-fold in cytoplasm, 14.0-fold in cell nuclei and membranes) and K (6.8-fold in cytoplasm) were detected after 59-days long culture. The Zn-regulating proteins metallothioneins showed significant changes in gene expression over time, with a potent down-regulation at RNA and protein level of the most abundant isoform in primary RPE cells, from 0.141 ± 0.016 ng·mL-1 at 10 days to 0.056 ± 0.023 ng·mL-1 at 59 days (0.4-fold change, p<0.05). Zn influx and efflux transporters were also deregulated, along with an increase in oxidative stress and alterations in the expression of antioxidant enzymes, including superoxide dismutase, catalase and glutathione peroxidase. The RPE cell model producing early accumulation of extracellular deposits provided evidences on an altered Zn homeostasis, exacerbated by changes in cytosolic Zn-binding proteins and Zn transporters, along with variations in other metals and metalloproteins, suggesting a potential role of altered Zn homeostasis during AMD development.